Assessing the Effects of Continuous Theta Burst Stimulation Over the Dorsolateral Prefrontal Cortex on Human Cognition: A Systematic Review - Ngetich, Ronald; Zhou, Jing; Zhang, Junjun; Jin, Zhenlan; Li, Ling (Frontiers in Integrative Neuroscience, 2020)
Theta burst stimulation is increasingly growing in popularity as a non-invasive method of moderating corticospinal networks. Theta burst stimulation uses gamma frequency trains applied at the rhythm of theta thus mimicking theta-gamma coupling involved in cognitive processes. The dorsolateral prefrontal cortex has been found to play crucial role in numerous cognitive processes. Here, we include 25 studies for review to determine the cognitive effects of continuous theta burst stimulation over dorsolateral prefrontal cortex; 20 of these studies are healthy participant while 5 are patient (Pharmacotherapy resistant depression) studies. Due to the heterogeneous nature of the included studies, only descriptive approach is used and meta-analytic ruled out. The cognitive effect is measured on various cognitive domains: attention, working memory, planning, decision making, executive function and inhibitory and cognitive control. We conclude that continuous theta burst stimulation over the dorsolateral prefrontal cortex mainly inhibits cognitive performance. However, in some instances it can lead to improved performance by inhibiting the effect of distractors or other competing irrelevant cognitive processes. Precisely, continuous theta burst stimulation over right dorsolateral prefrontal cortex impaired attention, inhibitory control, planning, and goal directed behaviour in decision making but also improved decision making by reducing impulsivity. Conversely, continuous theta burst stimulation over the left dorsolateral prefrontal cortex impaired executive function, working memory, and cognitive control but accelerating the planning decision making process. These findings constitute a useful contribution to the literature on the cognitive effects of the continuous theta burst stimulation over dorsolateral prefrontal cortex.